The After-Effect of Accelerated Intermittent Theta Burst Stimulation at Different Session Intervals - Yu, Fengyun; Tang, Xinwei; Hu, Ruiping; Liang, Sijie; Wang, Weining; Tian, Shan; Wu, Yi; Yuan, Ti-Fei; Zhu, Yulian (Frontiers in Neuroscience, 2020)
Objective: The study aims to investigate the after-effect of 3 sessions of intermittent theta bursts (iTBS) on mototr cortical excitability. The iTBS was induced over the primary motor cortex (M1) at different time intervals. Methods: The study has a cross-over design. Sixteen participants were assigned to 3 groups and received different accelerated iTBS protocols during each visit: (1) 3 continuous sessions with no interval (iTBS18000); (2) 3 iTBS sessions with 10 minutes intervals (iTBS600×3*10); (3) 3 iTBS sessions with 30 minutes intervals (iTBS600×3*30). As washout period, each visit is separated by at least 7 days. We measured the motor cortical excitability changes and intracortical inhibition. Results: A dose of 1800 pulses of accelerated iTBS per day is tolerable. The iTBS1800 led to a reduced cortical excitability; while iTBS600×3*10 and iTBS600×3*30 enhanced cortical excitability to a differential extent. After a total dose of 1800 pulses, iTBS600×3*30 exhibited the longer effect and highest percentage of individuals with enhanced cortical excitability. Conclusions: The results suggest that accelerated iTBS protocols at different time intervals result in different motor cortical excitability after-effects.